THE INFLUENCE OF BIG FIVE PERSONALITY TRAITS AND MOTIVATION ON STUDENT RESILIENCE IN MALAYSIAN UNIVERSITIES - Shafie, Dalili Izni; Mat Nawi, Farahiyah Akmal; Baistaman, Julaina; Nurcahyo, Rianto; Milhem, Marwan (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study investigates the influence of Big Five personality traits and motivation on student resilience among Malaysian university students. Personality traits: Openness, Conscientiousness, Extraversion, Agreeableness, and Neuroticism are established as core dimensions of individual differences, while motivation remains a central driver of academic performance and persistence. Drawing on Social Cognitive Theory and Self-Determination Theory, the study employed a quantitative survey design with data analyzed using Partial Least Squares-Structural Equation Modelling (PLS-SEM). The findings validated the proposed theoretical assumptions, demonstrating significant effects of both Big Five personality traits and motivation on student resilience, thereby supporting the study’s hypotheses (H1 and H2). The predictors explained a substantial proportion of the variance in resilience, with R² values ranging from 0.421 to 0.414. Importantly, the R² value of 0.414 exceeded Cohen’s (1988) recommended threshold of 0.26, affirming the robustness and stability of the research model. These results highlight that personality traits and motivation positively and meaningfully enhance resilience among students. The study contributes theoretically by bridging Social Cognitive Theory and Self-Determination Theory in understanding resilience, and practically by providing insights for universities and policymakers to develop targeted interventions that strengthen resilience and motivation. Such efforts are crucial to improving student well-being, adaptability, and academic success in Malaysia’s higher education context.